2011
DOI: 10.1088/0953-2048/24/3/035015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of superconductor–stabilizer interfacial resistance on quenching of a pancake coil made out of coated conductor

Abstract: We present the results of numerical analysis of normal zone propagation in a stack of Y Ba2Cu3O7−x coated conductors which imitates a pancake coil. Our main purpose is to determine whether the quench protection quality of such coils can be substantially improved by increased contact resistance between the superconducting film and the stabilizer. We show that with increased contact resistance the speed of normal zone propagation increases, the detection of a normal zone inside the coil becomes possible earlier,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…An approach to reduce or even avoid the shunt compromise in SFCLs and magnets is to intentionally increase the interfacial resistance (Ω·cm 2 ) between the HTS and the metallic shunt in order to increase the current transfer length (CTL). , This concept has proven that it can boost the NZPV of commercial tapes in a range of 25–100 times . Although effective, this method makes the CC impractical for applications where current leads (current contacts) are required for injecting current.…”
Section: Introductionmentioning
confidence: 99%
“…An approach to reduce or even avoid the shunt compromise in SFCLs and magnets is to intentionally increase the interfacial resistance (Ω·cm 2 ) between the HTS and the metallic shunt in order to increase the current transfer length (CTL). , This concept has proven that it can boost the NZPV of commercial tapes in a range of 25–100 times . Although effective, this method makes the CC impractical for applications where current leads (current contacts) are required for injecting current.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of papers have dealt with the stability and quench protection of YBCO coils [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] in a more microscopic fashion, including normal zone propagation along the conductor and between layers. Iwasa et al [24,25] first investigated these issues for YBCO coils and demonstrated that the YBCO-coated conductor must be loaded with several tens of µm thick copper stabilizer to provide coil stability and quench protection.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to focus on studying the quenching characteristic of YBCO material to realize the engineering application of R-SFCL. At present, many scholars have conducted extensive and in-depth research on the different characteristics of YBCO superconducting tape including quenching behavior under AC or DC overcurrent [15,16,17,18,19,20,21,22], quench propagation [23,24,25,26], quenching recovery [27,28,29,30], thermal and mechanical properties [31,32], minimum quench energy [33,34], maximum operating condition [35], and the effect of different materials on quenching behavior [36,37,38], which provide a solid foundation for the use of superconducting tape in design and fabrication of R-SFCL. However, there are few studies on common characteristics of quenching resistance of 2G HTS tape under AC and DC overcurrent, which is necessary and basic for R-SFCL design and research.…”
Section: Introductionmentioning
confidence: 99%